Perspektif Bioetika Islam dan Biopsikologi Konflik pada Kasus Kegagalan Aborsi yang Berdampak Kecacatan Anak - Ambar Sulianti; Endi Endi; Anwar Supenawinata (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2021)
Many unwanted pregnancies rampant on abortion practices. This research aims to arrange from the Islamic bioethic’s and biopsychology’s perspective on conflict of an abortion failure case and its effect on child's disability. This is a phenomenological study of a Muslim woman with experienced abortion failure and has a disabled child. Data were collected from interviews, observation, and analysis of prescription paper documents. The results showed she experienced a complete conflict phase from contradiction, attitude, to behavior phases. She has undernoge strong conflicts both in the decision-making and the abortion processes. This conflict from the perspective of Islamic bioethics relates to the obligation of a wife to obey the husband and the prohibition of fetal killing. The biopsychological perspective shows a combination of cognitive and affective subjects, through the hypothalamus-pituitary axis and the limbic system inhibits fetal growth. Biopsychological impacts include prolonged sadness, agitation disorders, sleep disorders, and psychosomatic gastrointestinal tract.